Fatigue study on the actuation performance of macro fiber composite (MFC): theoretical and experimental approach. (7th February 2017) - Pandey, Akash; Arockiarajan, A
Abstract: Macro fiber composite (MFC) is extensively used in vibration control and actuation applications due to its high flexibility and enhanced coupling coefficients. During these applications, MFCs are subjected to the continuous cyclic electrical loading, which may lead to the degradation in its actuation performance. In order to predict the life cycle of MFCs, an experimental setup has been devised and experiments are performed under cyclic loading condition. Efforts involved in the experiments are huge in terms of time and cost. Hence, an attempt has been made to develop a theoretical model to predict the fatigue behavior of MFCs. A nonlinear finite element method has been formulated based on Kirchhoff plate theory wherein the fatigue failure criterion based on strain energy is embedded. Simulated results based on the proposed model is compared with experimental observation and are in good agreement with each other. Variation in the life cycle of MFCs are also studied for different operating temperatures as well as structural/geometric configurations.